Relationships between leaf water potential and photosynthetic activity of field grapevines grown under different soil water regimes - Lopes, C.M. (1999)
Relationships between ecophysiological parameters from a grapevine irrigation experiment (rain-fed vs. deficit irrigation) conducted during 1998 at Alentejo, south of Portugal, with the red variety Aragonez (syn. Tempranillo) are presented and discussed. The irrigation affected positively grapevine physiology without changing berry composition. Predawn leaf water potential shows a significant dependence on available soil water, measured by a neutron probe, the correlation coefficients being higher in nonirrigated plants than in irrigated ones. Leaf water potential (Ψ) values measured in exposed leaves in the morning and afternoon were also significantly correlated with available soil water. Net CO2 assimilation rate (A) and stomatal conductance (gs) of sun leaves measured throughout the growing season at three different periods of the day were significantly correlated with predawn leaf water potential, nonirrigated vines presenting the highest correlation coefficients. Significant correlations were also found between Ψ and A or gs measured in the early morning. Our results show that, in water stress conditions, predawn leaf water potential can be used as an indicator of soil water availability and physiological activity of sun exposed leaves